Response in Growth Geronggang (Cratoxylon arborescens Vahl. Blume) Seddling by Giving Chicken Manure - Wirda Aprilia Ningsih; Muhammad Mardhiansyah; Pebriandi Pebriandi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Labuhanbatu, 2024)
One potential plant species for restoration in peat swamp forests is Cratoxylon arborescens. A well-managed nursery includes the application of chicken manure. This study aims to determine the effect and best dose of chicken manure fertilizer on the growth of Cratoxylon arborescens seedlings on peat planting media. This research used RAL (Completely Randomized Design) experimental method, which consisted of 4 treatments (P0 = control, P1 = 10% chicken manure + 90% peat, P2 = 30% chicken manure + 70% peat and P3 = 50% chicken manure + 50% peat) with 5 replications. The data obtained were analyzed statistically using variance analysis, followed by Duncan's New Multiple Range Test (DNMRT) at the 5% level. The results showed that chicken manure had a significant effect on the growth of Cratoxylon arborescens seedlings, because it was able to increase fertility and nutrient availability, improve the physical, chemical and biological properties of peat. The most effective and best treatment for four-month-old Cratoxylon arborescens seedlings was P2 (30% chicken manure + 70% peat) with 100% survival percentage, average height increase of 14.39 cm, average diameter increase of 1.56 mm, dry weight of 7.41 g and seedling robustness of 8.35